Reflections for a Sectoral Health Policy for Peru Based for on the National Health Accounts - Petrera, Margarita (Economía, 2017)
The objective of this article is to offer those responsible for the Peruvian health rectorship reflections on sectoral policy derived from the study of the country’s National Health Accounts (1995-2014). While it is true that the country has increased its spending on health from 4.4 to 5.2% of GDP, 33% of its total funding comes from household «out of pocket expense», which indicates that change is necessary. Problems in the responsiveness of the health system to greater funding and public expenditure, linked to issues of rectorship and service organization, are apparent.Although there has been an increase in numbers of people with insurance, the restrictions on what is covered prevent the great majority of these people accessing health services. The most important change in the public administration of expenditure has been decentralization, while in the private administration it has been the vertical integration of providers and insurers, which has given rise to a new agent: the health investor.The article concludes that the country is still far from being able to finance the aim of universal access to health care. Recommendations to improve the funding, joint administration, and expenditure point, almost simultaneously, towards generating greater public funding and social security within an active policy aimed at improving the global efficiency and institutionality ofthe system, which should work to the advantage of better health results as well to drastically decrease household pocket expense. Therefore, the success of the financial function is closely related to the adequate performance of the functions of rectorship and provision.